2023
DOI: 10.1021/acs.est.3c04487
|View full text |Cite
|
Sign up to set email alerts
|

Pyro-Catalytic Degradation of Pyrene by Bentonite-Supported Transition Metals: Mechanistic Insights and Trade-Offs with Low Pyrolysis Temperature

Sara B. Denison,
Peixuan Jin,
Priscilla Dias Da Silva
et al.

Abstract: Transition metal catalysts can significantly enhance the pyrolytic remediation of soils contaminated with polynuclear aromatic hydrocarbons (PAHs). Significantly higher pyrene removal efficiency was observed after the pyrolytic treatment of Fe-enriched bentonite (1.8% wt ion-exchanged content) relative to natural bentonite or soil (i.e., 93% vs 48% and 4%) at the unprecedentedly low temperature of 150 °C with only 15 min treatment time. DFT calculations showed that bentonite surfaces with Fe3+ or Cu2+ adsorb p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…15 Recently, we showed that ionexchanged Fe(III)-bentonite (i.e., Fe-bentonite) can be used as a catalyst to decrease the pyrolysis treatment temperature needed for high PAH removal. 19,20 We saw significantly higher pyrene removal efficiency using Fe-bentonite (93%) than natural bentonite (48%) or unamended contaminated soil (4%) at the unprecedentedly low temperature of 150 °C with only 15 min treatment time. 19 Density functional theory (DFT) shows that pyrene has stronger adsorption to clays with reducible Fe(III) sites than surfaces with less-reducible cationic transition metals (Cu(II) or Zn(II)), 19 and suggests that PAH pyro-catalytic treatment may be facilitated by direct electron transfer from the π-bonds of PAHs to cationic Fe(III) sites within the bentonite structure.…”
Section: ■ Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…15 Recently, we showed that ionexchanged Fe(III)-bentonite (i.e., Fe-bentonite) can be used as a catalyst to decrease the pyrolysis treatment temperature needed for high PAH removal. 19,20 We saw significantly higher pyrene removal efficiency using Fe-bentonite (93%) than natural bentonite (48%) or unamended contaminated soil (4%) at the unprecedentedly low temperature of 150 °C with only 15 min treatment time. 19 Density functional theory (DFT) shows that pyrene has stronger adsorption to clays with reducible Fe(III) sites than surfaces with less-reducible cationic transition metals (Cu(II) or Zn(II)), 19 and suggests that PAH pyro-catalytic treatment may be facilitated by direct electron transfer from the π-bonds of PAHs to cationic Fe(III) sites within the bentonite structure.…”
Section: ■ Introductionmentioning
confidence: 89%
“…19,20 We saw significantly higher pyrene removal efficiency using Fe-bentonite (93%) than natural bentonite (48%) or unamended contaminated soil (4%) at the unprecedentedly low temperature of 150 °C with only 15 min treatment time. 19 Density functional theory (DFT) shows that pyrene has stronger adsorption to clays with reducible Fe(III) sites than surfaces with less-reducible cationic transition metals (Cu(II) or Zn(II)), 19 and suggests that PAH pyro-catalytic treatment may be facilitated by direct electron transfer from the π-bonds of PAHs to cationic Fe(III) sites within the bentonite structure. 21 Such electron transfer would destabilize the PAH molecule by forming an aromatic radical, leading to subsequent polymerization and char formation.…”
Section: ■ Introductionmentioning
confidence: 89%
See 3 more Smart Citations